Anti-arthritic effects of Musa paradisiaca sapientum L. and Aloe vera L. in adjuvantinduced arthritic rats - SRI MULYANINGSIH; ENDANG DARMAWAN (Society for Indonesian Biodiversity, 2006)
Anti-arthritic effects of Musa paradisiaca sapientum L. and Aloe vera L. on the index responses of arthritic were investigated using adjuvant-induced arthritic rats. M. paradisiaca sapientum and A. vera pulp were blended into juice then the juices were administered orally on 17-30th day. To evaluate anti-arthritic effect of the juice, an arthritic rat model was developed using Complete Freund Adjuvant on 1-16th day. In addition, the research was divided into groups (n=5) including normal control groups, positive control groups, negative control groups, 3 groups were treated by M. paradisiaca juice at 50, 100, 200 mg/kgBW doses and the other groups were treated by A. vera juices at 1, 2 and 4 mg/kgBW doses. The indexes of arthritic were determined on 17th and 31st days then analyzed using ANOVA test and t test (p<0.05). The result showed that the indexes of arthritic rats were evidently decreased by either M. sapientum or A. vera juice. Moreover, indexes of arthritic to be closely restored to the normal levels through M. paradisiaca treatment at 50 mg/kg BW dose. In conclusion, both of juice is found to be effective in decreasing the inflammatory response and arthritic symptoms in adjuvant-induced arthritic rats.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Musa paradisiaca sapientum L., Aloe vera L., adjuvant-induced rat arthritic, indexes of arthritic